1986
DOI: 10.1002/1097-0142(19860315)57:6<1181::aid-cncr2820570619>3.0.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

Lobular carcinoma of the breast in a patient with klinefelter's syndrome. A case with bilateral, synchronous, histologically different breast tumors

Abstract: A case of bilateral breast cancer in a patient with a Klinefelter mosaic syndrome is presented. The tumor in the left breast was an infiltrating lobular carcinoma with characteristic in situ component. To the knowledge of the authors, this is the first case in the English literature of lobular carcinoma of the breast in a phenotypic man. In fact, it was the pathologic diagnosis which led to the study of the chromosomal abnormality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
5

Year Published

1988
1988
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(22 citation statements)
references
References 10 publications
0
17
0
5
Order By: Relevance
“…Lobular carcinoma is considered generally to be rare in men, and some authors have noted a higher proportion of papillary carcinoma than is usually reported in women. [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] Among studies that have included a review of the histologic material, only one from Denmark 9 is population based; many are from the older literature when the criteria for classification were different from those in current use, and none have exceeded 200 cases.…”
Section: Introductionmentioning
confidence: 99%
“…Lobular carcinoma is considered generally to be rare in men, and some authors have noted a higher proportion of papillary carcinoma than is usually reported in women. [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] Among studies that have included a review of the histologic material, only one from Denmark 9 is population based; many are from the older literature when the criteria for classification were different from those in current use, and none have exceeded 200 cases.…”
Section: Introductionmentioning
confidence: 99%
“…However, lobular carcinoma in the male breast is almost non-existent. Those cases diagnosed as lobular carcinoma probably arise in lobules formed during hyper-estrogenic states [22,23].…”
Section: Pathological Considerationsmentioning
confidence: 99%
“…En effet, dans le cas n o 1, le carcinome canalaire in situ est associé à deux mini-foyers infiltrants et dans le cas n o 3, il s'agit de canalaire in situ pur. Le carcinome lobulaire in situ est rare étant donné l'absence de lobules terminaux mais a été décrit en association avec le carcinome lobulaire invasif dans le cancer du sein chez l'homme [25]. Dans notre série, il n'a pas été décrit de carcinome lobulaire in situ sur les pièces d'exérèse.…”
Section: Histologieunclassified